Implementación de un objeto virtual de aprendizaje para habilidades comunicativas de los estudiantes de 8vo grado de Educación General Básica - Mancero Guaño, Johanna Esthefania (2025)
A virtual learning object for communication skills is an innovative pedagogical strategy that leverages technology to provide students with an interactive and motivating learning environment. The main objective of the research was to develop a virtual learning object for communication skills. The methodological approach applied within the research was the technological design methodology. The project focused on developing a technological educational resource for enhancing communication skills. The DICREVOA methodology was also used, which seeks to provide guidelines for the development of the tool. It consists of five phases that guide teachers in creating suitable resources within the educational field. The proposal focused on an innovative, participatory, and successful experience. These virtual learning objects typically include a variety of activities and multimedia resources, such as interactive exercises, educational games, videos, and reading materials, adapted to the needs and levels of eighth-grade students. To conclude, the project has produced an educational resource that will enable students and teachers in the Language and Literature field to engage in activities that promote these communication skills. The resource will be hosted and published in a website repository